Rough set-based dimensionality reduction for supervised and unsupervised learning - Shen, Qiang; Chouchoulas, Alexios (Zielona Góra: Uniwersytet Zielonogórski)
The curse of dimensionality is a damning factor for numerous potentially powerful machine learning techniques. Widely approved and otherwise elegant methodologies used for a number of different tasks ranging from classification to function approximation exhibit relatively high computational complexity with respect to dimensionality. This limits severely the applicability of such techniques to real world problems.
Keywords: knowledge-based systems; fuzzy rule induction; rough dimensionality reduction; knowledge acquisition